Dryingkinetics of Water Melon Seeds;WM-104 (Citrullus vulgaris) Undergoing Microwave - นาเสงี่ยม, ทัศนียา; นันทรัตน์, มัสยา; สังฆมะณี, ภานุวัฒน์; ปินะเต, วสันต์; นาชัยสินธุ์, มะลิ; ผาระนัด, วนิดา (Journal for Developing the Social and Community, 2015)
This study aimed to determine the dryingkinetics of water melon seeds;WM-104(Citrullus vulgaris) using microwave. Drying condition at microwave power level 3 levels were 500, 600, and 700 watts respectively, initial moisture content of water melon seeds approximate 345±0.11 gwater/gdry matter until a final moisture content approximate 12-13% dry basis. After drying process the qualities were investigated the color change, water activity, germination rate and growth of water melon seeds. The results showed that the drying rate increases with increasing higher microwave power levels. Drying atlowmicrowavepower levelsmakethebrightness valueslessthan thehigh microwavepower levels. The value in yellow color is increasedandthevaluein red color is negligiblydifferent. Thewater activity isin the rangesof 0.36-0.42. The germination rate and growth of water melon seeds have the same trend, namely atlowmicrowavepower levelssimilar towatermelonreference.